A review of methods and algorithms for optimizing construction scheduling - Zhou, Jingyang; Love, Peter; Wang, Xiangyu; Teo, Kok Lay; Irani, Zahir (Palgrave MacMillan, 2013)
Optimizing construction project scheduling has received a considerable amount of attention over the past 20 years. As a result, a plethora of methods and algorithms have been developed to address specific scenarios or problems. A review of the methods and algorithms that have been developed to examine the area of construction schedule optimization (CSO) is undertaken. The developed algorithms for solving the CSO problem can be classified into three methods: mathematical, heuristic and metaheuristic. The application of these methods to various scheduling problems is discussed and implications for future research are identified.